The Reflecting Back on the Role of the National Land Agency in Eradicating Land Mafia - Lingga, Firdo (International Journal of Law Society Services, 2024)
Land mafia is a serious problem that can harm society and the country. As a serious problem, BPN, which is a state instrument in structuring national land law, is mandated to be able to play an active role in eradicating the land mafia. This is not yet visible, because land mafia cases continue to increase, including in the Kendari City area.The approach method used in this writing is a qualitative method. Based on the studies carried out, it can be understood thatThe implementation of BPN's role in efforts to eradicate the land mafia in Kendari City is currently not optimal, this is because BPN acted after there were complaints from the public regarding the existence of land mafia cases in the community. The legal obstacle is the absence of regulations regarding the criminal law enforcement process in the Technical Instructions of the Ministry of Agrarian Affairs and Land Affairs Number 01/JUKNIS/D.VII/2018 concerning the Prevention and Eradication of Land Mafia. The next obstacle is the obstacle in the aspect of legal implementation which consists of internal and external obstacles. Internal constraints are constraints from the BPN institution. External obstacles are obstacles related to the legal culture in society regarding the eradication of the land mafia.